Avaliação de níveis de proteína digestível para girinos de rã-touro - Pinto, Donovan Filipe Henrique [UNESP] (2014)
Given the importance of growing tadpoles to get good results in frog farming, this study aimed to determine the digestible protein requirement for bullfrog tadpoles and evaluate the deposition of body nutrients. 9,120 bullfrog tadpoles were used, housed in 24 tanks and fed with isocaloric diets (3,676 kcal DE kg- 1) containing 21, 23, 25, 27, 29 and 31 % digestible protein (DP). We evaluated weight gain, feed intake, protein intake, food conversion, specific growth rate (SGR) and protein efficiency rate (PER). The Logistic model was used to describe the deposition of nutrients. The best estimated level to gain weight by segmented regression (broken line) was 27.7% DP. Feed intake decreased, the protein intake and SGR increased and the food conversion rate improved with increasing levels of PD. There was no statistical difference in the PER. Tadpoles fed diets with 27, 29 and 31% DP showed greater deposition of protein, water and ash and less fat